Development of spectrophotometric method for determination of mesalazine in pharmaceutical preparation - Dung, Nguyen Trung; Lan Anh, Nguyen Thi; Oanh, Dong Thi; Dung, Nguyen Hoang (Vietnam Journal of Chemistry, 2016)
A simple, rapid, sensitive and accurate spectrophotometric method for the determination of mesalazine in pharmaceutical preparation has been developed. The method is based on the reaction of mesalizine, with excessive nitrite, in an acidic medium, to produce the corresponding diazonium salt. After the removal of residual nitrite with sulphamic acid, the diazonium salt was coupled with N-(1-naphthyl)ethylenediamine (NEDA) in acidic medium to give a violet colored azo dye which has maximum absorption at 552 nm, the colored chromogen was stable for twenty four hours. Beer’s law is obeyed in the concentration range of 0.5-40.0 µg/ml (R2 = 0.999) with limit of detection (LOD) being 0.113 µg/ml. The molar absorptivities were 1.5.104 l.mol-1.cm-1 and Sandell’s sensitivity index of 0.0263 μg.cm-2. Recoveries of mesalazine from excipients were 95.4 -102.3 %. No interference was observed from common excipients present in pharmaceutical formulations. The proposed method has been applied successfully to determine mesalazine in pharmaceutical preparation as tablets (Pentasa and Sunmesacol). Keywords. Mesalazine, spectrophotometry, NEDA, Bratton-Marshall reagent, Pharmaceutical Preparation